Research Trends On Control Of Industrial Major Accident Hazard Occurrence In Malaysia: A Thematic Review - Mat Rashid, Rasyimawati; Radin Umar, Radin Zaid; Ahmad, Nadiah (Allied Business Academies, 2019)
Major Hazard Installation (MHI), which involves manufacturers undertaking industrial activities with hazardous substances have been one of the important industries contributing to the growth of Malaysia's economy. However, the nature of this industry brings with it risks that can threaten human lives, property destruction and environmental pollution. The "Control of Industrial Major Accident Hazard" (CIMAH) Regulations were gazetted by the Malaysian government in 1996 as a minimum safety guidance to ensure safe operations related to MHI processes. CIMAH Regulations has been enacted for more than two decades. However, there have been limited studies looking into the issues on control of major accident regulated by CIMAH. Therefore, the study aims to review publications related to the controls of the disaster occurrence respective to CIMAH Regulations. A systematic literature review method is carried out through multiple indexing databases. Publications from 1996 to 2018 were obtained and the controls discussed in the publications are classified into five main themes. The themes are: 1) governance of CIMAH Regulations, 2) the mitigation and prevention activities, 3) quantitative risk assessment, 4) the preparedness planning and 5) recorded a major accident. This provides an overview of the evolving knowledge related to CIMAH regulation controls in Malaysia.